Penerapan Elemen Menara Pada Bangunan Bergaya Art Deco Di Medan - Sari Desi Minta Ito Simbolon; Yunita Syafitri Rambe (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2022)
The characteristics of a building style and its character are shaped by some of its architectural elements. One of these architectural styles is an Art Deco-style building that has its own character. This style first appeared in 1925 and developed until 1940. This European architectural style was adopted in various American buildings due to their condition in the time of the industrial revolution. The modern architectural movement that developed at that time also influenced the art deco style and gave it a modern touch. The Art Deco style in graphic design restores again decorativism but not necessarily in the form of ornaments. Decorative impressions can be achieved through the play of elements geometric, typographic blocks, textures and shades of color. Art Deco style has characteristics that are very distinctive and easily distinguished from other architectural styles. Art deco still exists in the spirit of medan city development as place of research evidenced by the many old buildings that are repurposed as well as new buildings that take the characteristics of Art Deco. One of them is the use of tower elements or one part of the building that rises slightly upwards and gives a magnificent impression.